Study on dynamic response of debris flow to pipeline with defect. (November 2022) - Jiang, Hongye; Ding, Hongchao; Li, Wei; Chi, Minghua; Li, Youlv; Yang, Wenbo
Highlights: Bingham fluid model is used to simulate debris flow impact process. The overall displacement of pipeline is mainly caused by mud impact. The dominant factor of pipeline failure with defect changed from mud impact to stone impact compared with intact pipeline. Strain range of pipeline with defect diffuses from defect area to surrounding under debris flow impact. Abstract: Based on the Finite Element Method (FEM) and the Smooth Particle Hydrodynamics (SPH) coupling method, this paper established full-size multi-physical field coupling model of debris flow impacting pipeline. By simplifying mud into Bingham fluid, this paper studied the dynamic response law of pipeline with defect and intact pipeline (pipeline without defect) under the joint action of mud and block stone, established the displacement equations of the pipeline under impact, thus obtained the displacement, stress and strain characteristics of different pipeline positions at different impact moment. The results showed that numerical simulation of dispersing mud into SPH particles can well simulate the movement process of mud splashing and detour flow. The maximum displacement occurred in the middle part of the pipeline. For the intact pipeline, the main failure was caused by the instantaneous impact of the mud, however, for the pipeline with defect, the dominant failure factor changed from the mud impact to the stone impact. This study provided a new pathway and theoretical reference for disaster prevention and control of pipelines in debris flow section.